SISTEM PENJUALAN BATIK BERBASIS WEB PADA BAYU ART SEMARANG (Information Technology and Telematics, 2013)
ABSTRACT   Sales service is very important when  competition among  employers  increasingly  stringent.  Development  of information  systems  for  online   sales  makes  it  easy  for employers to increase sales services infinite space and time. Media sales online is  also capable of being a medium of information entrepreneurs to achieve corporate strategic goals. Similarly, in Bayu Art Semarang which in this case  would like to introduce batik products to buyers all over the world by  making  batik  SALES  SYSTEM   BASED  ON  WEB BAYU ART Semarang.   Keywords: Batik, web, sales